2018
DOI: 10.31235/osf.io/kmqhd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“There is Nothing Inherently Mysterious about Assistive Technology” A Qualitative Study about Blind User Experiences in US Academic Libraries

Abstract: Eighteen academic library users who are blind were interviewed about their experiences with academic libraries and the libraries’ websites using an open-ended questionnaire and recorded telephone interviews. The study approaches these topics from a user-centered perspective, with the idea that blind users themselves can provide particularly reliable insights into the issues and potential solutions that are most critical to them. Most participants used reference librarians’ assistance, and most had positive exp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…One recent study involved an interview with 18 blind students about their experiences with academic libraries and the libraries' websites. Findings indicated that the students felt that the more librarians knew about assistive technology, the more helpful they could be in providing assistance for research, whether using the technology themselves or knowing enough to provide relevant verbal cues (Mullikan, 2017). This was another aspect under consideration for our study.…”
Section: Ebsco Information Services Usability Studymentioning
confidence: 96%
“…One recent study involved an interview with 18 blind students about their experiences with academic libraries and the libraries' websites. Findings indicated that the students felt that the more librarians knew about assistive technology, the more helpful they could be in providing assistance for research, whether using the technology themselves or knowing enough to provide relevant verbal cues (Mullikan, 2017). This was another aspect under consideration for our study.…”
Section: Ebsco Information Services Usability Studymentioning
confidence: 96%
“…What visually oriented readers regard as a simple task such as getting advice online for a web product/service may not be trivial for a screen reader user [ 1 ]. As expressed by a user who had limited experience with screen readers, intensive navigating through the library’ websites took much longer time (twice or three times as much) to search for information compared to visually oriented readers [ 2 ]. Though screen readers assist users greatly, limitations exist and need to be resolved to provide more accessible use.…”
Section: Introductionmentioning
confidence: 99%